2018
DOI: 10.1016/j.jaac.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Impact of Eveningness Chronotype (“Night-Owls”) in Youth: A Randomized Controlled Trial

Abstract: Objective: To determine whether an intervention to reduce eveningness chronotype improves sleep, circadian, and health (emotional, cognitive, behavioral, social, physical) outcomes. Method: Youth aged 10 to 18 years with an evening chronotype and who were “at risk” in 1 of 5 health domains were randomized to: (a) Transdiagnostic Sleep and Circadian Intervention for Youth (TranS-C; n = 89) or (b) Psychoeducation (PE; n = 87) at a university-based clinic. Treatments were 6 individual, weekly 50-minute sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 63 publications
2
69
1
Order By: Relevance
“…Intriguingly, a recent cognitive‐behavioral intervention conducted with adolescents with an evening chronotype not only improved adolescent‐ and parent‐reported sleep, but also resulted in a decrease in evening circadian preference, an earlier endogenous circadian phase (i.e. dim light melatonin onset), and less weeknight–weekend discrepancy in total sleep time and wake time (Harvey et al., ). No studies have tested behavioral sleep interventions in adolescents with ADHD; testing cognitive‐behavioral and other interventions for improving sleep and daytime outcomes is an important area for investigation (Becker, ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a recent cognitive‐behavioral intervention conducted with adolescents with an evening chronotype not only improved adolescent‐ and parent‐reported sleep, but also resulted in a decrease in evening circadian preference, an earlier endogenous circadian phase (i.e. dim light melatonin onset), and less weeknight–weekend discrepancy in total sleep time and wake time (Harvey et al., ). No studies have tested behavioral sleep interventions in adolescents with ADHD; testing cognitive‐behavioral and other interventions for improving sleep and daytime outcomes is an important area for investigation (Becker, ).…”
Section: Discussionmentioning
confidence: 99%
“…The second aim was to examine the effects of TranS‐C (vs. PE) on risks in five health domains at 6‐month follow‐up, and whether they were maintained from posttreatment to 6‐month follow‐up. We also conducted exploratory analysis for specific measures comprising the composite risk scores to understand the TranS‐C effects further and be consistent with the previous report on the pre‐post effects (Harvey et al, ). We hypothesized that TranS‐C would demonstrate greater improvements than PE in both sleep and circadian outcomes and risks across health domains at 6‐month follow‐up and that TranS‐C treatment effects would be maintained from posttreatment to 6‐month follow‐up.…”
Section: Introductionmentioning
confidence: 56%
“…Parents or guardians of all participants provided informed consent and participants provided informed assent. A detailed study procedure was reported elsewhere (Harvey et al, ). Participant flow was illustrated in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations